New circular polarization selective surface - Ren, Zhilin (Nanyang Technological University, 2022)
Circular Polarization Selective Surface (CPSS) has significant advantages in improving reception sensitivity, enhancing channel capacity, and overcoming multi-path interference, and has been widely used in modern wireless communication systems. In this thesis, the research status of CPSS is systematically summarized, and a new design method is studied. Aiming at the fundamental technical problems in the design process, some innovative ideas and technical means are put forward based on the basic structure and working mechanism. The main research contents can be summarized in the following aspects: (1)Through extensive investigations, the analysis and design methods of the miniaturized broadband circular polarization antennas are summarized, the conventional and classical antenna technologies and models are studied, and the working principles of the related antenna structures are analyzed. (2)This thesis summarizes the current technology and development status of phase shifters and focuses on the structure and principle of the Schiffman phase shifter and the subsequent improvement. (3)Based on a wideband circular polarizer with parallel metal strip lines, this research optimizes the size, distribution, and shape of the metal strips to reach the goal of broadening bandwidth and smaller thickness. The axial ratio (AR) is improved to 68% from 54%, and the thickness is 2.5 mm smaller than the previous design. In order to break the size bottleneck of miniaturization design by conventional antenna design method, a phase shifter coupled with microstrip line structure is added to further improve the bandwidth and thickness performance. At last, the AR bandwidth increases from 8.77% to 61.58%. The thickness of the structure is decreased from 8.7 mm to 5 mm.